Analisis Hukum Terhadap Perseteruan Antara Organisasi Kemasyarakatan dan Purnawirawan dalam Konteks Negara Hukum di Indonesia - Ida Muidah; Masharin; Adhe Permana; Eko Purwanto; Witandri; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Conflicts between community organizations (ormas) and retired military/police personnel in several cases have led to legal violations, including hate speech, incitement, and physical violence. This article aims to analyze the aspects of constitutional law and criminal law related to these conflicts, as well as the state's responsibility in ensuring public order. The research employs a qualitative method with a statutory and case study approach. The analysis shows that weak law enforcement against community organizations and related actors reflects the state's inconsistency in upholding the principles of the rule of law. The state has a constitutional obligation to ensure that freedom of association is not misused for political interests and violence.